Software for virtual reality in interior design - Gustina, Yusuf (University Malaysia Sarawak, UNIMAS., 2005)
This study aims to identify the comparison four different kinds of the software for Virtual Interior Design. Four of the software for Virtual Interior Design are Virtual Reality Modelling Language (VRML), OpenGL, C'Nedra and INT3D System which is the software that can be use to design and develop the virtual environment. Each of the software is deeply focus on the advantages, strengths, limitations and similarity. The method use for evaluating the software is by comparing the characteristic of the software and by looking at the early case study from previous researchers. In this study, researcher try to use one of the software which is called VRML to design and develop the virtual environment and it involves the system design and system development which is discuses detail in chapter 4 and 5. After being compared, this research will come up with the solutions and the future recommendation for other researcher. As for the findings, researcher find that each of the software have it own advantages and the strengths in CIder to support the virtual reality environment. for overall, this study helps the system developer to improve the limitation of the software and recommend for future research on others application.